2020
DOI: 10.1016/j.annonc.2020.08.1124
|View full text |Cite
|
Sign up to set email alerts
|

1008P IMbrave150: Management of adverse events of special interest (AESIs) for atezolizumab (atezo) and bevacizumab (bev) in unresectable HCC

Abstract: Background: Conventional transarterial chemoembolization (cTACE) is an effective locoregional therapy in hepatocellular carcinoma (HCC). We evaluated variations around cTACE in a-fetoprotein (AFP), circulating cell-free and tumor DNA (cfDNA and ctDNA) as a marker of therapeutic response.Methods: This prospective monocentric study enrolled consecutive patients treated by cTACE with samples collected at baseline (D-1), day 2 (D+2) and at 1 month (M+1). All cTACE were carried out by only one interventional radiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…An analysis of time to onset of first AEs of particular relevance with atezolizumab and bevacizumab in the IMbrave150 study showed that the earliest atezolizumab-defined AEs were infusion-related reaction (onset at median 0.7 months), pancreatitis (1.4 months), and hepatitis (1.6 months); rash and hyperthyroidism occurred at a median of 2.7 months, hypothyroidism at 3.5 months, and diabetes mellitus at 4.4 months. 39 The earliest bevacizumab-defined AE was hypertension (onset at median 1.5 months), followed by proteinuria and venous thromboembolic events at 2.8 months, bleeding or haemorrhage at 3.3 months, and arterial thromboembolic events at 4.7 months. 39 The onset of GI symptoms is most commonly 5–10 weeks after initiation of immune checkpoint inhibition.…”
Section: Monitoring and Management Of Aes Associated With Atezolizuma...mentioning
confidence: 96%
See 2 more Smart Citations
“…An analysis of time to onset of first AEs of particular relevance with atezolizumab and bevacizumab in the IMbrave150 study showed that the earliest atezolizumab-defined AEs were infusion-related reaction (onset at median 0.7 months), pancreatitis (1.4 months), and hepatitis (1.6 months); rash and hyperthyroidism occurred at a median of 2.7 months, hypothyroidism at 3.5 months, and diabetes mellitus at 4.4 months. 39 The earliest bevacizumab-defined AE was hypertension (onset at median 1.5 months), followed by proteinuria and venous thromboembolic events at 2.8 months, bleeding or haemorrhage at 3.3 months, and arterial thromboembolic events at 4.7 months. 39 The onset of GI symptoms is most commonly 5–10 weeks after initiation of immune checkpoint inhibition.…”
Section: Monitoring and Management Of Aes Associated With Atezolizuma...mentioning
confidence: 96%
“…39 The earliest bevacizumab-defined AE was hypertension (onset at median 1.5 months), followed by proteinuria and venous thromboembolic events at 2.8 months, bleeding or haemorrhage at 3.3 months, and arterial thromboembolic events at 4.7 months. 39 The onset of GI symptoms is most commonly 5–10 weeks after initiation of immune checkpoint inhibition. 57…”
Section: Monitoring and Management Of Aes Associated With Atezolizuma...mentioning
confidence: 96%
See 1 more Smart Citation
“…2022;16 (9): [31][32][33][34][35][36][37][38][39] At present, 20 courses of therapy have been carried out in this regimen, and the stabilization of the disease is maintained. Against the background of the ongoing therapy, no adverse events were noted, including immune-mediated ones that required the abolition or reduction of doses of drugs.…”
Section: иммунотерапия опухолейmentioning
confidence: 99%
“…В исследовании IMbrave150 кровотечения как осложнения лечения зарегистрированы у 25% больных на комбинированной терапии «атезолизумаб + бевацизумаб» и в 17% случаев в группе сорафениба, однако геморрагические осложнения 3-4-й степени регистрировались одинаково -в 6% в обеих группах 1 [24,[34][35][36][37].…”
Section: Immunotherapy For Tumorsunclassified